Subversion of host cell signaling: The arsenal of Rickettsial species - Huang, Dan; Luo, Jingjing; OuYang, Xuan; Song, Lei (Frontiers in Cellular and Infection Microbiology, 2022)
Rickettsia is a genus of nonmotile, Gram-negative, non-spore-forming, highly pleomorphic bacteria that cause severe epidemic rickettsioses. The spotted fever group and typhi group are major members of the genus Rickettsia. Rickettsial species from the two groups subvert diverse host cellular processes, including membrane dynamics, actin cytoskeleton dynamics, phosphoinositide metabolism, intracellular trafficking, and immune defense, to promote their host colonization and intercellular transmission through secreted effectors (virulence factors). However, lineage-specific rickettsiae have exploited divergent strategies to accomplish such challenging tasks and these elaborated strategies focus on distinct host cell processes. In the present review, we summarized current understandings of how different rickettsial species employ their effectors’ arsenal to affect host cellular processes in order to promote their own replication or to avoid destruction.